Pengaruh Penggunaan Metode Resitasi Terstruktur untuk Meningkatkan Hasil Belajar Siswa - Rachmawati Racmawati; Ria Herdhiana; Sungging Handoko (Program Studi Pendidikan Ekonomi, FKIP Universitas Langlangbuana, 2016)
Structured recitation method is a tool that is expected to improve student learning outcomes, because basically structured recitation method is principled to students where students can learn freely but can account for the results. The purpose of this study to determine the effect of using structured recitation method to improve student learning outcomes. The research was conducted at SMK Binawarga Bandung Jalan Buahbatu No. 135 held in class X Ak-1 and X Ak-2. The method used is an experiment that uses structured recitation methods with the students as the object being studied and the data source. The instruments used in supporting this research are: learning tools (syllabus and learning scenarios), observation sheets, questionnaires, tests (initial and final tests Processing and data analysis is done quantitatively The results of this study indicate that there are differences in the improvement of learning outcomes students between experimental classes using structured recitation methods and control classes using conventional methods, thus structured recitation methods have an effect to improve student learning outcomes.